Hyperoodon planifrons Flower 1882 - James H. Honacki; Kenneth E. Kinman; James W. Koeppl (Alien Press, Inc. & The Association of Systematics Collections, 1982)
Hyperoodon planifrons Flower, 1882. Proc. Zool. Soc. Lond., 1882:392. TYPE LOCALITY: Australia, Western Australia, Dampier Arch., Lewis Isl. DISTRIBUTION: Southern Hemisphere, circumpolar, temperate to antarctic waters; occasionally into tropical waters. PROTECTED STATUS: CITES - Appendix II as Order Cetacea. ISIS NUMBER: 5301411005002002001. Published as part of James H. Honacki, Kenneth E. Kinman & James W. Koeppl, 1982, Order Cetacea, pp. 290-304 in Mammal Species of the World (1 st Edition), Lawrence, Kansas, USA :Alien Press, Inc. & The Association of Systematics Collections on page 300, DOI: 10.5281/zenodo.7352983